2007
DOI: 10.1007/s11240-007-9293-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of several factors on somatic embryogenesis and plant regeneration in protoplast cultures of Gentiana kurroo (Royle)

Abstract: Protoplasts were isolated from cell suspensions derived from cotyledon and hypocotyl Gentiana kurroo (Royle). Cell walls were digested with an enzyme cocktail containing cellulase, macerozyme, driselase, hemicellulase and pectolyase in CPW solution. Protoplast viability ranged from 88 to 96%. Three techniques of culture and six media were evaluated in terms of their efficiency in producing viable cultures and regenerating whole plants. With liquid culture, cell division occurred in only a low number of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…The calli derived from sLD and liquid culture systems were non-embryogenic, while those derived from aPL culture system showed both embryogenic and non-embryogenic characteristics. The effects of various culture systems on callus formation from protoplasts have also been reported in other plants [7,8,15,24]. In Gentiana kurroo, globular somatic embryos were detected one week after the microcolonies obtained in the thin layer culture and bead culture had been transferred to induction medium, but the cell aggregates obtained in the liquid culture died when transferred to the same medium [15].…”
Section: Plantlet Regenerationmentioning
confidence: 65%
See 1 more Smart Citation
“…The calli derived from sLD and liquid culture systems were non-embryogenic, while those derived from aPL culture system showed both embryogenic and non-embryogenic characteristics. The effects of various culture systems on callus formation from protoplasts have also been reported in other plants [7,8,15,24]. In Gentiana kurroo, globular somatic embryos were detected one week after the microcolonies obtained in the thin layer culture and bead culture had been transferred to induction medium, but the cell aggregates obtained in the liquid culture died when transferred to the same medium [15].…”
Section: Plantlet Regenerationmentioning
confidence: 65%
“…In Oenothera hookeri, embedding protoplasts in thin alginate layers was considered one of the most crucial parameters for cell division and colony formation [23]. In Gentiana kurroo, the plating efficiency of protoplasts reached 68.7% using agarose bead culture [15]. We also tested the effect of culture methods on protoplast division and colony formation.…”
Section: Protoplast Culturementioning
confidence: 99%
“…The presence of aneuploid cells (5-6C) in some calli of G. kurroo in the present study resulted in the regeneration of a single plant, which, however, showed abnormal morphology and did not survive. In our previous studies on G. kurroo, about 30-37 % polyploids (tetraploids and hexaploids) was regenerated from cell suspensionderived protoplasts (Fiuk and Rybczyński 2007), and 14 % tetraploids from hypocotyl-derived cell suspension (Fiuk and Rybczyński 2008a).…”
Section: Ploidy Of Cells Of Callus and Regenerated Plantsmentioning
confidence: 99%
“…Recently, we succeeded in regenerating plants from leaf mesophyll protoplasts of G. decumbens by indirect somatic embryogenesis (Tomiczak et al 2015). PRM3 medium containing 1.0 mg l -1 kinetin, 0.5 mg l -1 GA 3 , 80 mg l -1 adenine sulfate, which led to the formation of somatic embryos from protoplast-derived tissues of G. decumbens, was the same medium as was widely used for the induction of somatic embryogenesis from callus and cell suspensions of G. pannonica, G. cruciata, G. tibetica (Mikuła and Rybczyński 2001;Mikuła et al 2002), and G. kurroo (Fiuk and Rybczyński 2008a), as well as from protoplasts of G. kurroo cell suspensions (Fiuk and Rybczyński 2007). The greatest number of somatic embryos regenerated from mesophyll protoplast-derived callus of G. tibetica and G. kurroo was also achieved by using this medium.…”
Section: The Influence Of Culture Conditions On Callus Proliferation mentioning
confidence: 99%
See 1 more Smart Citation